The potential of waqf-blended finance using crowdfunding in Indonesia - Hassan, M. Kabir; Nurul Meirama Irsya,; Aishath Muneeza, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Significant obstacles to the development of Islamic charitable endowment (waqf) in Indonesia include the lack of accountability, limited financing, and mismanagement. One way to remove these obstacles is implementing waqf-blended finance, a newly developed model (therefore unexplored) that integrates waqf and commercial finance. The current research aims to explore the potential of crowdfunding for waqf-blended finance. The underlying assumption is that crowdfunding can help boost waqf fundraising and resolve liquidity and transparency issues in fund collection and distribution. Therefore, exploring the application of crowdfunding in waqf blended finance is essential. Improving waqf-blended financing itself is necessary because it can ensure project profitability. This study applies a qualitative approach with three stages of analysis: desk research, semi-structured interviews, and data analysis. The semi structured interviews aim to discover the current practices of the key stakeholders. The data collected from the literature review and interviews were analysed to assess the potential of waqf blended finance concept, build a waqf-blended finance model, and estimate the model’s implementation challenges. The analysis covers both the external and internal challenges of waqf development in Indonesia, with the former being prioritized over the latter due to its more significant influences. The discussion encompasses the potential of two waqf-blended financing models, emphasising the critical role of crowdfunding and banks as waqf administrators (nazir). Since this study is the first to investigate the feasibility of crowdfunding in waqf-blended finance development in Indonesia, it offers a novel contribution to the field. From the findings, we propose considerations in the implementation of a waqf-blended financing model in Indonesia.